ln (x+1)^2 =2

We know that ln x^y = y ln x

==> ln (x+1)^2 = 2*ln (x+1) = 2

Now divide by 2:

==> ln (x+1) = 2/2=1

==> x+1 = e^1 = e

==> x = e-1

==> **x = 1.7183 (approx.)**

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now